Ultraviolet Metasurfaces of ≈80% Efficiency with Antiferromagnetic Resonances for Optical Vectorial Anti‐Counterfeiting. Issue 5 (4th April 2019) - Huang, Kun; Deng, Jie; Leong, Hai Sheng; Yap, Sherry Lee Koon; Yang, Ren Bin; Teng, Jinghua; Liu, Hong
Abstract: Metasurfaces enable the full control of electromagnetic waves over a wide spectrum. High‐efficiency transmissive metasurfaces have been demonstrated up to the visible frequencies by using dielectrics. However, extending the operating spectrum to the ultraviolet range is challenging. This is due to the strong absorption in typical dielectric materials and the inexhaustive understanding of the magnetic resonances in dielectric nanostructures. Here, a large‐bandgap material—niobium pentoxide (Nb2 O5 )—is introduced to engineer the ultraviolet geometric meta‐holograms to achieve a total efficiency of 79.6% at 355 nm wavelength. The employed orientation‐varying nanobricks, operating as miniaturized half‐waveplates (HWPs), are elaborately designed to excite the antiferromagnetic modes that maintain Ex component of the incident light via even antiparallel magnetic dipoles (AMDs) but reverse Ey component via odd AMDs, thereby unveiling the underlying mechanism of dielectric nano‐HWPs. By adding the polarization degree of freedom, an ultra‐channel meta‐hologram, multiplexing two orthogonal spin channels while exhibiting three outputs, is demonstrated experimentally for ultraviolet vectorial anti‐counterfeiting. This work might open the door toward high‐performance ultraviolet nanophotonics and meta‐optics. Abstract : Large-bandgap semiconductor materials of Nb2 O5 are employed to engineer ultraviolet metasurface holograms made of dielectric nanobricks to achieve ≈80% efficiency, which is devised to support antiferromagnetic resonances. The ultra‐channel holograms are demonstrated be able to output three polarization‐dependent images for the application of optical vectorial anti‐counterfeiting.